2000
DOI: 10.1177/019874290002600104
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Behavioral Problems and Language Delays in Boys and Girls Enrolled in Head Start Classrooms

Abstract: Early emergent patterns of behavioral problems, social skill deficits, and language delays were examined in 259 three-year-old children enrolled in Head Start classrooms. The Child Behavior Checklist for Children Ages 2 to 3 (CBCL/2–3) and the Social Skills Rating System (SSRS, Pre-School Version) were completed by the children's primary caregivers. Language skills were assessed using the Preschool Language Scale (PLS)-3 and the Peabody Picture Vocabulary Test (PPVT)-III. Findings indicated that this populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(77 citation statements)
references
References 34 publications
1
72
1
3
Order By: Relevance
“…For example, Kaiser, Hancock, Cai, Foster, and Hester (2000) found that boys scoring high on a measure of problem behavior were about 50% more likely to have low language scores than boys with low behavior scores. Qi and Kaiser (2004) reported a correlation of -.32 between Head Start children's scores on a teacher rating of the frequency of their internalizing problem behaviors and a measure of their expressive language skills.…”
Section: The Link Between Poor Oral Vocabulary Skills and Poor Behaviormentioning
confidence: 99%
“…For example, Kaiser, Hancock, Cai, Foster, and Hester (2000) found that boys scoring high on a measure of problem behavior were about 50% more likely to have low language scores than boys with low behavior scores. Qi and Kaiser (2004) reported a correlation of -.32 between Head Start children's scores on a teacher rating of the frequency of their internalizing problem behaviors and a measure of their expressive language skills.…”
Section: The Link Between Poor Oral Vocabulary Skills and Poor Behaviormentioning
confidence: 99%
“…Language difficulties and ED appear to emerge from the same etiological and environmental risk factors (e.g., Kaiser, Hancock, Cai, Foster, & Hester, 2000;Kaiser & Hester, 1997) and are likely to co-occur (Benner et al, 2002). Furthermore, research suggests that externalizing behaviors are related to language skills whereas internalizing behaviors are not (Nelson et al, 2005).…”
Section: Hypothesismentioning
confidence: 99%
“…Feil, Walker, Severson, and Ball (2000) surveyed 954 parents of children (3-4 years old) enrolled in Head Start and found 52% of the children met criteria for referral to mental health services for behavior and emotional problems. Other studies have reported a range of 20-33% for behavior problems in young children from lower SES backgrounds (Gross, Sambrook, & Fogg, 1999;Kaiser, Hancock, Cai, Foster, & Hester, 2000). Most available studies that have included poverty as a contextual variable in the development and maintenance of behavior problems in young children have tended to examine children in special programs such as Head Start or in clinicreferred samples.…”
mentioning
confidence: 99%